Kuat Lentur Balok Tanpa Tulangan dengan Kemiringan Sambungan 45o di Setengah dan Seperempat Bentang - Herlambang, Fajar Surya; Purnawirati, I.G.A. Neny (Jurnal Talenta Sipil, 2025)
Concrete casting processes in projects often cannot be completed in a single, continuous pour. This can be due to staged construction methods, extensive casting areas resulting in large concrete volumes, or limitations in manpower, equipment, and materials. Consequently, construction joints become necessary. This study aims to identify how variations in the inclination of joints in unreinforced concrete beams affect their flexural strength. Additionally, it seeks to compare the flexural strength between unreinforced beams with varying joint inclinations to determine if there are significant differences in their load-carrying capacity. The research method involves casting several unreinforced concrete beam specimens with identical dimensions but varying joint inclinations. A flexural testing machine is then used to apply concentrated or distributed loads to these specimens. A common point of contention in the field is where the concrete casting should ideally be stopped. This research aims to address this question. The approach involves testing the flexural strength of concrete beams measuring 15x20x120 cm with a concrete compressive strength (f'c) of 20 MPa. These beams are unreinforced, allowing for the observation of concrete behavior without the influence of reinforcement. The beam casting is carried out in two stages with a 1-day interval between pours, and the joint inclination is set at 45 degrees. The joints are positioned at ¼ and ½ of the beam span. Concrete adhesive is added to the joints as a reinforcement measure. Flexural strength tests are conducted at concrete ages of 14, 21, and 28 days. The test results indicate that all beams with joints fractured at the joint, with the fracture pattern following the joint line. Overall, the flexural strength of beams with joints decreased by up to 75%. Therefore, incomplete concrete casting processes result in concrete joints that pose equal risks, and it cannot be determined whether joining at ¼ or ½ of the span is preferable. This demonstrates that concrete joints are vulnerable points prone to flexural failure